The Precision of the Overall Data-Model Fit for Different Design Features in Confirmatory Factor Analysis - Almaleki, D. (Engineering, Technology & Applied Science Research, 2021)
Factor Analysis (FA) is the study of variance within a group. Within-Subject Variance (WSV) is affected by multiple features in a study context such as the Experimental Design (ED) or the Sampling Design (SD). The aim of this study is to provide an empirical evaluation of the influence of different aspects of ED and SD on WSV in the context of FA in terms of model precision. The study results showed that the precisions of the overall model fit indices TLI and CFI, as functions of VTF, STV, h2, and their interaction, varied, as did the precisions of the overall model fit indices GFI, AGFI, and RMSEA as functions of VTF, STV, and their interactions. Overall, when the VTF is 4:1 or 7:1, the required STV is 16:1 or above 32:1 or above to show precision in factor solution.